Esthesioneuroblastoma: A Patterns-of-Care and Outcomes Analysis of the National Cancer Database. Issue 5 (22nd February 2018) - Orton, Andrew; Boothe, Dustin; Evans, Daniel; Lloyd, Shane; Monroe, Marcus M; Jensen, Randy; Shrieve, Dennis C; Hitchcock, Ying J
Abstract: BACKGROUND: The available literature to guide treatment decision making in esthesioneuroblastoma (ENB) is limited. OBJECTIVE: To define treatment patterns and outcomes in ENB according to treatment modality using a large national cancer registry. METHODS: This study is a retrospective cohort analysis of 931 patients with a diagnosis of ENB who were treated with surgery, radiation therapy, and/or chemotherapy in the United States between the years of 2004 and 2012. Log-rank statistics were used to compare overall survival by primary treatment modality. Logistic regression modeling was used to identify predictors of receipt of postoperative radiotherapy (PORT). Cox proportional hazards modeling was used to determine the survival benefit of PORT. Subgroup analyses identified subgroups that derived the greatest benefit of PORT. RESULTS: Primary surgery was the most common treatment modality (90%) and resulted in superior survival compared to radiation ( P < .01) or chemotherapy ( P < .01). On multivariate analysis, PORT was associated with decreased risk of death (hazard ratio [HR] 0.53, P < .01). PORT showed a survival benefit in Kadish stage C (HR 0.42, P < .01) and D (HR 0.09, P = .01), but not Kadish A (HR 1.17, P = .74) and B (HR 1.37, P = .80). Patients who received chemotherapy derived greater benefit from PORT (HR 0.22, P < .01) compared with those who did not (HR 0.68, P = .13). Predictors of PORT included stage, grade, extent of resection, and chemotherapy use. CONCLUSION: Best outcomes were obtained in patients undergoing primary surgery. The benefit of PORT was driven by patients with stages C and D disease, and by those also receiving chemotherapy.